Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMAN 1 Indralaya - Indra Wedi (UNISAN JURNAL, 2024)
This research aims to explore and analyze the role of the principal's leadership in improving teacher performance at SMAN 1 Indralaya. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, observation and documentation studies. Respondents consisted of school principals, teachers, administrative staff and students. The data analysis technique uses a thematic approach. The research results show that the leadership of the school principal has a crucial role in improving teacher performance in the school. The principal plays a role as the main driver in creating a conducive work environment and motivating teachers to improve the quality of their teaching. Leadership strategies that are inclusive, supportive and build effective communication have proven to be effective in improving teacher performance. Apart from that, school principals are also responsible for developing teacher professionalism through continuous training and development. They facilitate teachers' access to the resources and support needed to improve the quality of their teaching. In addition, transformational leadership has been proven to have a significant positive impact on teacher performance, by motivating them to innovate and collaborate in achieving school goals. In conclusion, the leadership role of the principal is very important in improving teacher performance at SMAN 1 Indralaya. Effective leadership not only creates a work environment that allows for teacher professional growth, but also shapes a school culture that is oriented towards learning and collaboration. The implication of this research is the need to develop leadership training programs for school principals to improve the quality of education in secondary schools.